Light seeing in patients with brain tumors and head and neck malignancies treated with radiotherapy - Farzin, Mostafa; Molls, Michael; Astner, Sabrina; Reitz, Silvia; Kreiser, Kornelia; Kampfer, Severin (European Journal of Oncology and Environmental Health, 2017)
Background:Reaching a better understanding of light vision in radiotherapy patients. Materials and methods: 20 patients with brain tumors and head and neck malignancies who received radiotherapy and experienced any kind of light or color vision during radiation treatment. All the components of visual pathway were contoured. Results: 11 patients were male and 9 were female (median age: 56 years). The range of dose/fraction and total prescribed dose were 1.8-3Gy and 36-70.4Gy respectively. Twelve patients reported white, 11, blue, 2, yellow and 2, gray color visions. Seven patients experienced more than one color, while 2 patients did not attribute any special color to their experiences. Four patients had a kind of smell experience and 1 patient had a taste experience. Conclusion: Cherenkov radiation in eye balls may be the origin of light seeing experiences in patients receiving radiation treatment for head and neck malignancies, since treatmentsareperformed with ionizing radiations with energycapable to produce this effect. Also this effectmay be due to phosphenes produced by radiation treatment in different parts of the visual pathway (from retina to visual cortex). In order to investigate the mechanism of this phenomenon in patients and to define a radiation dose threshold – if the origin of this phenomenon is phosphenes produced in visual pathway – larger studies are needed.